Gas Lift and Electric Submersible Pump Combination used to Activate a Dead Well - Tsamo, Nestor; Kenmogne, Nazaire Pierre; Tokoue Ngatcha, Dianorré; Mbenoun, Josper Karl; Nyang Kibanya, Noel; Kamdem, Lazarre (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The well-called KD-2 (for confidential reasons) is not producing because the bottom hole pressure of the well is greater than the reservoir pressure. The purpose of this paper is to activate the well KD-2 by the gas lift and electric submersible pump (ESP) with a rotating gas separator combination in order to increase its production. The completion and the pressure, volume, and temperature (PVT) data are processed under Pipesim and by integrating a certain number of calculations by the nodal analysis and the decline curve methods. The results obtained show that well KD-2 activated by the gas lift provides a flow rate of 3038.019 STB/day. In order to increase the flow rate of well KD-2 activated by the gas lift, the ESP with rotating gas separator is added and the flow rate becomes 4845.325 STB/day which represents a gain of 59.48% in flow rate. In addition, the gas lift and ESP with rotating gas separator combination guarantees an eight-year operating period for a probability of 3,601,197 with a return on investment of 2 months. The gas lift and ESP with rotating gas separator gas combination can be used to optimize the production of low-flow wells in the same geographical areas and to consider the reactivation of dead wells.